2022
DOI: 10.1002/2475-8876.12275
|View full text |Cite
|
Sign up to set email alerts
|

Influence of residential performance on residents' health status (part II): Nationwide survey of environmental performance of apartment buildings and residents' health status

Abstract: The residential environment clearly affects health. For example, a previous study has established relationships between specific environmental factors and the health status of residents in detached houses. However, studies focused on apartment buildings are still insufficient. Therefore, in this study, a large nationwide questionnaire survey of residents of apartments was conducted. The residential environment was subjectively evaluated using a Japanese Comprehensive Assessment System for Built Environment Eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
(84 reference statements)
0
0
0
Order By: Relevance
“…In addition, the impact of housing on subjective well-being is about one-fifth that of subjective health, which is significant, given that health and well-being are often analyzed as the same concept [21]. In addition, previous studies have shown that the housing environment has a significant influence on residents' health [2,3], and indirect influences from housing to subjective well-being through health are expected to exist. The importance of housing will be further enhanced if indirect effects from housing to subjective well-being are identified.…”
Section: Housing Hierarchy Of Needs Leading To Subjective Well-beingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the impact of housing on subjective well-being is about one-fifth that of subjective health, which is significant, given that health and well-being are often analyzed as the same concept [21]. In addition, previous studies have shown that the housing environment has a significant influence on residents' health [2,3], and indirect influences from housing to subjective well-being through health are expected to exist. The importance of housing will be further enhanced if indirect effects from housing to subjective well-being are identified.…”
Section: Housing Hierarchy Of Needs Leading To Subjective Well-beingmentioning
confidence: 99%
“…People spend 60%-70% of their day at home, and thus housing is infrastructure that plays an important role in residents' well-being [1]. In fact, poor-quality housing environments have been strongly linked to a wide range of health problems, including cardiovascular and respiratory diseases, injuries, and mental health [2][3][4][5][6][7][8][9]. Furthermore, a house is one of the most important assets for many families; for example, home ownership is a crucial indicator of social capital, reflecting safety, independence, and privacy [10].…”
Section: Introductionmentioning
confidence: 99%